(untitled) (Experimental biology, 2015)
The epidermal growth factor receptor (EGFR), family of receptor tyrosine kinases, also known as ErbB1 or HER1, plays crucial roles in the development of multicellular organisms. Mutations and over-expression of the EGF-receptors have been implicated in a variety of diseases. The extracellular, ligand binding regions of EGFR are quite heavily sialylated. Here we designed a lectin-metabolic assay that allows direct comparison of cell surface sialylation between health and disease states. We utilize two human mammary epithelial cell lines, HB4A (breast normal cells) and T47D (breast cancer cells) as a model system for the assessment of differential sialylation extracellular domain of ErbB1. Under starved condition, sialic acid treatment of both cells resulted increased lectin fluorescence signals that indicated the accumulation of more sialic acids in the metabolic state as demonstrated by Western blotting and immuno-precipitation. Furthermore, lectin-precipitation showed a very strong MAL-I (Maackia amurensis agglutinin I) binding on the EGFreceptors of sialic acid treated T47D cells suggesting an increase of Neu5Acα2→3Gal on the cell surface. The MAL-I lectin can be used for discrimination at molecular level between healthy and diseased cells.